The impact of special exercises to develop the skill of the players transmitter accuracy tennis wheelchairs for men - Mohammed, Ahmed; Majed, Hydar (Journal of Physical Education, 2015)
There are many sports in which they participated with disabilities Among the most prominent of these sports tennis wheelchairs as it is for the game of tennis sports task, that play a role in the preparation of the individual both physically and psychologically , mentally and socially through the development of their abilities and their potential for positive participation in community service and the evolution in this game and widening its base is one of the aspects that reflect the amount of real value is as a game of tennis wheelchairs task GamesIt has received considerable support from the International Tennis Federation ITF)) International Tennis Federation , as in his support for the game of tennis healthy so the attention included the development of two games together in all aspects, the importance of research lies in the preparation exercises a private vehicle to develop the strength and accuracy of some basic skills Btens wheelchair players National team for men